MILITER DALAM KEJAHATAN PERANG JEPANG TERHADAP INDONESIA TAHUN 1942 - 1945 STUDI KASUS: PERBUDAKAN SEKSUAL WANITA INDONESIA - Zafarayana, Dantika Lavinia; Putranti, Ika Riswanti (Journal of International Relations, 2019)
Japan's participation in World War II against allies encouraged Japan to carry out aggression in East Asian and Southeast Asian countries, including Indonesia. After the Japanese landing in Indonesia on 1942, the Japanese military carried out various policies, one of it was sexual slavery or jugun ianfu. Thousands of Indonesian women were made into Japanese military sex slaves. Women's International War Crimes Tribunal (WIWCT) on Japan's Military Sex Slavery was held in 2000, which judge 10 Japanese war crimes defendants. Jugun ianfu is a systemic crime organized by the Japanese military. This study aims to explain the driving factors of the Japanese Military in committing war crimes against Indonesia in the form of sexual slavery during World War II 1942-1945. This study using historical research method and the library search for data collection. Organizational Culture theory of Constructivism will be used to explain the driving factors of Japanese military commit sexual slavery. This study found that what prompted the Japanese military to commit sexual slavery in Indonesia was influenced by two factors. First, the Japanese military doctrine that is the Imperial Rescript Armed Forces which demanded military compliance with all orders from the Japanese Emperor. Secondly, the doctrine of the Japanese Emperor who ordered the establishment of the jugun ianfu system itself, so that the Japanese military carried out the establishment of a jugun ianfu system in its occupying countries, including Indonesia.